Management of Severe Warm Autoimmune Hemolytic Anemia in Chronic Systemic Lupus Erythematosus - Putu Enrico Pramana Okaniawan; Ajib Zaim Alamsyah; Dwiputra Yogi Pramarta (Journal of Social Research, 2026)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with multi-organ involvement, often complicated by hematologic disorders such as warm autoimmune hemolytic anemia (AIHA). AIHA in SLE patients can lead to severe anemia, jaundice, organ dysfunction, and increased mortality, yet data on its management, particularly in severe cases, remain limited. This study aimed to describe the diagnosis, management, and clinical outcomes of severe warm AIHA in a patient with chronic SLE. A qualitative case report methodology was employed, collecting data through anamnesis, physical examination, laboratory testing, imaging studies, and treatment documentation. The patient, a 28-year-old female with chronic SLE, presented with severe normochromic-normocytic anemia, jaundice, splenomegaly, and discoid lesions. Management included methylprednisolone pulse therapy, hydroxychloroquine, packed red cell transfusions, supportive care, and vitamin D supplementation. Clinical monitoring demonstrated progressive improvement in hemoglobin levels, reduction in autoimmune activity, and resolution of systemic symptoms over five days of hospitalization. The study concludes that integrated medical and supportive therapies are effective for stabilizing severe warm AIHA in chronic SLE, emphasizing the need for individualized care and close monitoring. Future research should focus on larger cohorts to validate treatment protocols, explore adjunctive therapies, and identify predictive markers for severe hemolysis to enhance early diagnosis and improve long-term patient outcomes.